Preparation of CuO/CeO2 Catalyst with Enhanced Catalytic Performance for Water–Gas Shift Reaction in Hydrogen Production. Issue 6 (17th May 2018) - Chen, Chongqi; Zhan, Yingying; Li, Dalin; Zhang, Yanjie; Lin, Xingyi; Jiang, Lilong; Zheng, Qi
Abstract: CuO/CeO2 is a promising catalyst for water–gas shift (WGS) reaction in H2 production. Much effort has been devoted to improving its catalytic activity and stability by CeO2 support modification or introduction of secondary active species. Here a method to enhance the catalytic performance by controlling the deposition rate of copper is reported. The nature of CuO and CuO‐CeO2 synergetic interaction are modulated by using different copper sources (Cu(NO3 )2 and Cu[(NH3 ) ] 4 2 + ) and controlling reaction temperatures. The as‐prepared CuO‐CeO2 catalysts show distinguish catalytic performances for the WGS reaction. The one prepared by using Cu[(NH3 ) ] 4 2 + at the reaction temperature of 30 °C (CuCe‐ 30N ) shows superior catalytic activity and stability. The CuCe‐ 30N catalyst possesses the largest Cu 0 surface area (39.2 m 2   g cat - 1 ) and strongest CuO‐CeO2 synergetic interaction. The largest Cu 0 surface area provides the most active sites for CO adsorption thus leading to its highest activity. The strong synergetic interaction prevents Cu crystallites from sintering during the WGS reaction, thus improving its thermal stability. Abstract : Cu 0 surface area and CuO‐CeO2 synergetic interaction of CuO/CeO2 catalyst can be modulated by controlling the deposition rate of copper. They are shown to be positively correlated to the catalytic activity of CuO‐CeO2 for water gas shift reaction.